DESIGN STRATEGY OF BATAK SOCIO-CULTURAL PARK AS A TOURIST DESTINATION WITH LOCAL WISDOM APRROACH IN LAKE TOBA REGION - Bernad Arifin Pasaribu; Made Suastika; Sri Yuliani (Universitas Sebelas Maret Surakarta, 2018)
Indonesia is a country that has various ethnics and cultures. One of the tribes found in Indonesia is Batak tribe located in North Sumatra, Batak tribe can be divided into six sub-tribe of Batak Karo, Toba, Simalungun, Mandailinng, Angkola, Pakpak. In today's modern era, cultural degradation has caused the values of the nation being eroded so that these cultures need to be preserved to avoid them from extinction. This study describes the idea of accommodating activities that are preserving the culture of the Batak tribe as a Batak socio-cultural park. Not only accommodate, Batak socio-cultural park is also functioned as a tourist destination which will support the main function of preserving culture and introducing Batak culture to the wider community. The design method that will be applied is by applying the Batak’s local wisdom to the architecture of the Batak socio-cultural Park building to give a traditional impression and be able to be an attraction for tourists to come to visit. The results of the research are strategies to design a Batak socio-cultural park as a tourist destination by accommodating elements of local wisdom.